1996
DOI: 10.1021/om950571d
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and X-ray Structures of Anionic Sodocene Sandwiches

Abstract: While, the lithocene anion (Cp2Li-) can simply be generated by reacting 2 equiv of CpLi with PPh4Cl in THF, the attempted synthesis of the sodocene anion under similar reaction conditions results in the crystallization of [Cp-][PPh4 +]. The structure consists of “naked” Cp anions pinched between metaphenyl hydrogens of the phosphonium cations. An ansa-sodocene anion in which the two Cp rings are bridged by a −C(Me)2−C(Me)2− chain is obtained by reaction of Me4C2(C5H4Na)2 with 1 equiv of PPh4Cl in THF. Its crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 22 publications
6
46
0
3
Order By: Relevance
“…This was also observed in the structures of the lithocene [1] and sodocene [4] anions (Figure 3). These interactions can be regarded as CH´´´Cp hydrogen bonds between the C dÀ ± H d dipole and the negatively charged p-electron system of the Cp ring.…”
Section: Sjoerd Harder*supporting
confidence: 67%
See 1 more Smart Citation
“…This was also observed in the structures of the lithocene [1] and sodocene [4] anions (Figure 3). These interactions can be regarded as CH´´´Cp hydrogen bonds between the C dÀ ± H d dipole and the negatively charged p-electron system of the Cp ring.…”
Section: Sjoerd Harder*supporting
confidence: 67%
“…[4] This is due to the much higher acidity of a tetrabutylphosphonium group compared to a tetraphenylphosphonium group.…”
Section: Sjoerd Harder*mentioning
confidence: 99%
“…Figure 11 shows that an off-centre C À H donor slightly directs itself to the edge of the Cp ring, which suggests that the CÀH´´C angles should also be considered. The angles for each CÀH´´´C and CÀH´´´Cp c contact, together with their average value hYi, are given in [24,14,25] Anionic alkali metallocenes can also function as donors in CÀH´´´Cp À hydrogen bonding. Detailed analyses of their crystal structures show that networks of intermolecular bonding do indeed exist (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is the same as that drawn from the dissociation energies. [28][29][30] c. M-side and M-middle mean the distances of M to the center of the above and the middle ring…”
Section: Dissociation Energy and Homo-lumo Gapmentioning
confidence: 99%
“…Due to their special structures, properties, and extensive applications, a variety of binuclear and multinuclear metallocenes have been intensively studied experimentally and theoretically since the identification of the ferrocene (Cp 2 Fe) structure in 1952 [4,6,[23][24][25][26][27][28][29][30]. Frenking et al reported the geometries and metal-ligand bond dissociation energies of an inverted sandwich [E-Cp-E'] + complex (E, E'= group 13 element; Cp =cyclopentadienyl) [31].…”
Section: Introductionmentioning
confidence: 99%